Volunteer Tourism Program Development, Case Vietnam Heritage Travel - Nguyen, Leminh (Rovaniemen ammattikorkeakoulu, 2012)
The purpose of this thesis project is to figure out what kinds of volunteer tourism programs should be developed for Vietnam Heritage Travel, a tour operator in Vietnam, and what business and volunteering factors need to be considered for the development. In order to answer those research questions, the thesis reviewed current studies and researches on volunteer tourism, including its definitions, theoretical frameworks and practices, various types of projects worldwide and overview of volunteer tourism in Vietnam. This empirical knowledge provided general referential backgrounds to generate relevant ideas and service/product concepts for volunteer tourism program development. Next, to transform a service/product concept to an end-user product, there is a need of comprehensive know-how in product development, particularly Tourism Product Development (TPD) in a holistic approach and perspective. Certain exemplary and emerging strategic economic tools and methods were highlighted and analysed in the thesis, such as “experience economy”, co-creation/coopetition concepts and practices, and eight frameworks for TPD developed from a case research study in Northern Finland. Finally, a quantitative research, which was a Webropol online survey, was conducted, which then confirmed previous empirical research and revealed certain business and volunteering factors: favourite volunteer project types (wildlife/ environmental, community development, education, women/minorities/youth, and scientific research), most popular sources of information (internet/social media/forums/online communities and friends/past experience), most important purchasing factors of a volunteer tourism program offered by a profit-making company (cost, types/activities/experience and destinations), a balance between altruism and profit gained, and a balance between altruism and personal development/achievement. Effectively, the theoretical backgrounds and research results can provide useful references and suggestions for a volunteer tourism program ...